Association of nutrition and immune-endocrine dysfunction with muscle mass and performance in cognitively impaired older adults. (March 2018) - Tay, L.; Leung, B.P.; Wee, S.; Tay, K.S.; Ali, N.; Chan, M.; Lim, W.S.
Highlights: Muscle quality beyond muscle mass impacts on functional performance in cognitively impaired older adults. Malnutrition is associated with both pre-sarcopenia and sarcopenia. A pro-inflammatory and endocrine deficient state aggravates decline in muscle quality with consequent frank sarcopenia. Abstract: Background: With lean mass declining early in Alzheimer's disease, muscle quality beyond quantity is relevant to physical performance. We sought to identify potentially modifiable factors for the differential loss of muscle mass (pre-sarcopenia) and its performance (sarcopenia) in older adults with mild cognitive impairment (MCI) and mild-to-moderate Alzheimer's disease (AD). Methods: This is a cross-sectional study of 108 community-dwelling older adults with MCI and mild-to-moderate AD. Participants were categorized as: (i) No sarcopenia (normal muscle mass), (ii) Pre-sarcopenia (low muscle mass without weakness or slowness), (iii) Sarcopenia (low muscle mass AND weak grip strength and/or slow gait speed) using Asian cut-offs. Muscle quality was defined as the ratio of grip and knee extension strength to average arm and leg lean mass respectively. We measured cognitive, functional and physical (Short Physical Performance Battery, SPPB) performance; physical activity level; nutritional status; and blood biomarkers of inflammation and endocrine dysfunction. Results: SPPB (p = 0.033) and activity level (p = 0.010) were highest in the pre-sarcopenic group. Pre-sarcopenic group had highest arm muscle quality [10.6 (7.7–12.2) vs 13.9 (12.6–15.7) vs 11.3 (9.7–12.8), p < 0.001], despite significantly lower appendicular lean mass than non-sarcopenic group. In multi-nomial logistic regression reference to non-sarcopenic group, malnutrition independently increased risk for both pre-sarcopenia (Relative risk = 7.53, 95% C.I 1.20–47.51, p = 0.032) and sarcopenia (Relative risk = 11.91, 95% C.I 2.85–49.77, p = 0.001). A combined pro-inflammatory and endocrine deficient state significantly increased the risk of sarcopenia (Relative risk = 5.17, 95% C.I 1.31–20.37, p = 0.019). Conclusion: Malnutrition is a precursor for progressive loss of muscle mass, but a pro-inflammatory and endocrine deficient state may potentially aggravate decline in muscle quality to culminate in frank sarcopenia.